Evidence-Based Approach through a Critical Look at Strategic Management Theories - Vahid Khashei Varnamkhasti; Elham Sadat Sabour Abvani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Current changes suggest that organizations’ efforts to adapt to external conditions for survival have been more natural than Conscious efforts. Strategies are evolving as a result of the urgent need to respond to market changes - the same need that has a role in making organizational hierarchy flat - this elimination of management layers, in turn, affects the ways in which organizational strategies are created. Since the 1990s, following the failure of prescriptive strategic plans, a new paradigm in the field of strategic management and decision-making called evidence-based approach has emerged. This research has been done in the insurance industry and while having a pathological view of strategic decisions that are taken at the head of insurance companies, the researcher has tried to find a model of strategic decision-making based on evidence from the discourses of senior managers of insurance companies. This research is fundamental in terms of purpose and it is among the mixed exploratory studies. In this study, first the evidence-based strategic decision model was designed using the Grounded theory and the Strauss and Corbin paradigm model, and then the fuzzy Delphi method was used in order to determine the importance of the factors identified in the model.